Anti-Gay, Sexist, Racist: Backwards Italy in British News Narratives. Issue 1 (22nd March 2018) - Filmer, Denise
The Berlusconi years have witnessed Italy placed in the uncomfortable spotlight of the international media; however, now that Berlusconi's power has waned, a timely reflection is due on the extent to which the vestiges of the former Premier's cultural have coloured images of Italy in British news discourse. How far do cultural myths influence the selection, narration and reception of Italian news reported in British newspapers? Do Berlusconi's verbal gaffes reverberate in the construal of newsworthiness and evaluative parameters, reinforcing and perpetuating stereotypes of Italians as a whole? These are the key issues this contribution attempts to address. Stemming from a broader research project on the representation of Berlusconi's non politically correct language in the British press, this study examines the representation of certain aspects of Italian culture that have been the focus of British news narratives in recent years. Four recurring themes are explored and discussed: homophobia, racism, sexism and fascism. Implementing a critical discourse analysis approach, news texts retrieved from a cross-section of British newspapers reporting on Italian affairs are examined. The analysis then focuses on the invisibility of translation in reconstructing discursive events in news narratives across cultural and linguistic barriers, and suggests that decisions taken in translation solutions can reproduce and reinforce myths or stereotypes.